2015
DOI: 10.1136/annrheumdis-2015-eular.5265
|View full text |Cite
|
Sign up to set email alerts
|

AB0311 Superiority of Ultrasound over Clinical Examination in Detecting Tenosynovitis in Rheumatoid Arthritis

Abstract: BackgroundIn rheumatoid arthritis (RA), tendon pathology is a well-recognized, but underestimated aspect of the disease, which may lead to irreversible functional impairment and consequent disability. Clinical joint examination is less time-consuming than ultrasound (US) but it may misdiagnosis tenosynovitis (TS).ObjectivesThe aim of this study was to compare clinical assessment of tenosynovitis detection with US examination.MethodsA cross sectional study was performed including patients followed-up for active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Tenosynovitis (TS) of hand and wrist tendons is common in early untreated inflammatory polyarthritis. 1 However, clinical examination alone may not detect this pathology, 2 especially as conventional rheumatoid arthritis (RA) disease activity scoring systems focus on joints, not tendons. The use of MRI and ultrasound examination is more sensitive and has shown that the prevalence of detecting TS in patients with early RA is higher than by physical examination alone.…”
Section: Introductionmentioning
confidence: 99%
“…Tenosynovitis (TS) of hand and wrist tendons is common in early untreated inflammatory polyarthritis. 1 However, clinical examination alone may not detect this pathology, 2 especially as conventional rheumatoid arthritis (RA) disease activity scoring systems focus on joints, not tendons. The use of MRI and ultrasound examination is more sensitive and has shown that the prevalence of detecting TS in patients with early RA is higher than by physical examination alone.…”
Section: Introductionmentioning
confidence: 99%